Peningkatan Hasil Belajar Matematika Menggunakan Model Pembelajaran Problem Based Learning (PBL) - Rokhayah, Siti (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to improve Mathematics learning outcomes using the Problem Based Learning (PBL) learning model. This research is classroom action research with the research subject of grade VIII-B MTs Negeri 3 Bantul students. Research is carried out in 2 cycles and each cycle consists of 2 meetings, covering 4 stages, namely planning, implementation, observation and reflection. Data collection of learning outcomes is obtained by end-of-cycle tests and processed quantitatively. The results showed that there was an increase in mathematics learning outcomes of grade VIII-B MTs Negeri 3 Bantul students on the